Students' Understanding of the Concept of Usury (Riba) and Its Impact on Life: A Qualitative Study of Islamic Economics Students at Mulawarman University - Muhammad Romli (FEB Universitas Mulawarman, 2025)
This study is about understanding what Sharia Economics students at Mulawarman University know about the concept of usury. We also want to see how it affects their life. We used a method to do this. This method is called approach. We collected data by talking to students, in depth watching what they do and looking at documents. We did this with 10 students who started school between 2021 and 2024. What we found out is that most students know the idea of usury. They think of it as something that's not fair like adding extra money to a debt or when buying and selling things, which is not allowed in Islam. The students understood the topic in ways. Some of the students had a better understanding of the whole thing. They really got how bad usury is. Usury has a bad impact on people. It can cause problems for individuals like getting stuck in debt feeling stressed and losing the things in life. Usury also causes problems for the community like people not being treated equally economic problems and people not helping each other much. The impact of usury is bad for the community and, for individuals it can lead to inequality, economic injustice and weakened solidarity and for individuals it can cause debt traps, stress and loss of blessings